An analysis on a public university final year engineering students’ stress levels - Haslinda, Hashim; Anita, Abdul Rani; Nor Yazi, Khamis; Azwin Arif, Abdul Rahim; Zuraina, Ali; Zubair, Khalil; Adam Shariff Adli, Aminuddin; Nor Akmar, Nordin (Universiti Malaysia Pahang, 2021)
Stress is one of the serious issues that affect university students’ life and has been identified to cause academic decline, poor relationships with peers and family members and overall dissatisfaction with life. As for final year university students, academic workloads, expectations from societies and future career uncertainties are some of the common factors that create stress. Therefore, this case study aims to investigate the stress experienced by the final year engineering students at a public university. The main objectives are to identify factors that cause stress and its effects on the students. A five-dimension set of questionnaires i.e. Interpersonal, Intrapersonal, Motivation, Environment, and Workload was distributed to 260 final year students of an engineering faculty before they participated in a Stress Management Awareness Program. The program which was part of the Final Year Project (FYP), exposed the students with stress management strategies. Later, interviews were conducted to explore the extent of stress effects on the students’ academic success, and lifestyle in general, and the effect of the workshop. The mean scores of the dimensions and its items were analysed descriptively and findings from the interviews were compared after the students had undergone the workshop. The quantitative results indicated a moderate level of stress among the students with some significance in ‘Environment’ and ‘Workloads’ dimensions. Qualitatively, the workshop had made the students aware of their stress experiences, and educated them with various stress management strategies. Interestingly, there were similar continuous patterns of stress experiences from 33 volunteered interviewees, which have brought to light the actual circumstances of students’ stress. Evidently, these results call for a context-driven stress management module that can provide the students with resourceful selfregulated strategies in coping with the demanding life as final year engineering students.